Research at the College of Aeronautics Cranfield - Murphy, A. J. (College of Aeronautics, 1960)
The 1,142nd lecture to be given before the Society and the 37th Main lecture to be held at a Branch Centre " Research at the College of Aeronautics " by Professor A. J. Murphy. M.Sc., F.R.Ae.S., F.I.M., Principal, College of Aeronautics, was given under the auspices of the Cambridge Branch on 21st January 1960. Professor W. A. Mair, M.A., F.R.Ae.S., Francis Mond Professor of Aeronautical Engineering, University of Cambridge, and President of the Cambridge Branch, opened the proceedings and then handed over to the President of the Society, Mr. Peter G. Masefield, M.A., F.R.Ae.S., Hon.F.I.A.S., M.Inst.T.